2016
DOI: 10.1364/oe.24.018388
|View full text |Cite
|
Sign up to set email alerts
|

Complete hyperentangled Bell state analysis for polarization and time-bin hyperentanglement

Abstract: We present a complete hyperentangled Bell state analysis protocol for two-photon four-qubit states which are simultaneously entangled in the polarization and time-bin degrees of freedom. The 16 hyperentangled states can be unambiguously distinguished via two steps. In the first step, the polarization entangled state is distinguished deterministically and nondestructively with the help of the cross-Kerr nonlinearity. Then, in the second step, the time-bin state is analyzed with the aid of the polarization entan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 72 publications
0
33
0
Order By: Relevance
“…Hyper-entanglement within energy-time entangled states. Hyper-entangled states are quantum states which are entangled in two or more independent degrees of freedom 23,26,36,43 , such as polarization, optical paths, or orbital angular momentum. Since these degrees of freedom can be controlled autonomously, such systems can be best described as multi-partite states, where each degree of freedom represents an independent party 23,36 .…”
Section: A-b Andmentioning
confidence: 99%
“…Hyper-entanglement within energy-time entangled states. Hyper-entangled states are quantum states which are entangled in two or more independent degrees of freedom 23,26,36,43 , such as polarization, optical paths, or orbital angular momentum. Since these degrees of freedom can be controlled autonomously, such systems can be best described as multi-partite states, where each degree of freedom represents an independent party 23,36 .…”
Section: A-b Andmentioning
confidence: 99%
“…In quantum communication, hyperentanglement can be used to increase the channel capacity largely, besides its application for assisting the implementation of quantum communication protocols based on one DOF. HBSA is the prerequisite for quantum communication protocols with hyperentanglement, and it is one of the important parts in high-capacity quantum repeaters [36][37][38][39][40][41][42][43][44][45]. We have reviewed the high-capacity long-distance quantum communication protocols based on polarization-spatial hyperentanglement, including the complete HBSA scheme with the cross-Kerr nonlinearity, the quantum teleportation of a quantum state in both the polarization and the spatial-mode DOFs with polarization-spatial hyperentanglement, and the hyperentanglement swapping of polarization-spatial hyperentangled Bell states.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Li and Ghose [41] presented a very simple scheme for the self-assisted complete maximally hyperentangled state analysis via the cross-Kerr nonlinearity and another interesting HBSA scheme [42] for polarization and time-bin hyperentanglement. Up to now, there are several important schemes for the analysis of hyperentangled states [36][37][38][39][40][41][42][43][44][45], including the probabilistic one based on linear optical elements [44] and the one for hyperentangled Greenberger-Horne-Zeilinger (GHZ) states [45]. In 2015, Wang et al [66] demonstrated in experiment the quantum teleportation of an unknown quantum state of a single photon in multiple DOFs by implementing the HBSA of two-photon systems probabilistically with linear optical elements and ancillary entanglement sources.…”
Section: High-capacity Quantum Communication With Hyperentanglementmentioning
confidence: 99%
See 1 more Smart Citation
“…These DoFs can be used to construct hyper-entanglement, which refer to the entangled in multiple DoFs of a quantum system simultaneously. Recently, hyper-entanglement becomes a promising quantum resource due to its high capacity of channel, and it has extensive applications in quantum information processing, such as Bell-state analysis with hyper-entanglement [38][39][40][41][42][43][44], quantum repeaters [45], entanglement swapping [42,46,47], hype-entanglement concentration [48,49], and so on. So far, experimental progress of hyper-entanglement generation has been reported using different photonic DoFs [50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%